MASS MEDIA AND THE LEGITIMATION OF INTERNET CONTROL IN RUSSIA: THE CASE OF TELEGRAM - Wijermars, Mariëlle (AoIR Selected Papers of Internet Research, 2018)
In today's hyperconnected world, states are confronted with the global challenge of responding to potentially disruptive online communications, such as terrorist propaganda and fake news. Formulating effective internet regulation to address these threats carries the risk of infringing upon media freedom and constitutional rights. In the case of Russia, ostensibly sound legitimations have been instrumentalised to bring about a dramatic decline in internet freedom. Controlling public opinion may well be decisive for Russia's "success" in expanding its system of internet controls without arousing popular resistance. Scholarship thus far, however, has neglected to critically examine how the Russian government legitimates and cultivates popular support for restricting online freedom of speech. This paper aims to address this crucial aspect of internet censorship by studying how restrictions of internet freedom, freedom of expression and the right to information and privacy are framed in political and media discourses. The paper presents a case study examining the legitimation of user data storage, surveillance and restriction of online anonymity, on the example of messaging application Telegram. To justify legal measures in these domains, policymakers have framed their proposals as anti-terrorist, or claimed the need to protect personal data from foreign states. Typically, anonymity and privacy are recast as secrecy indicating criminal (e.g., drug dealers) or morally derogatory intent (e.g., paedophilia). The paper analyses how frames are produced by policymakers; how they are translated and disseminated in state and (semi-)independent media; and how they resonate in online debates and social media.